IMPLEMENTASI PENDIDIKAN KARAKTER PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKN) SISWA KELAS V SDN KP. BULAK III PAMULANG - Aldi Sutisna; Ina Magdalena; Romi Ramdon Ginanjar (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2022)
This study aims to determine the implementation of Character Education Implementation in Citizenship Education (PKn) Subjects for Class V SDN Kp. Bulak III Pamulang. The research method used in this research is descriptive qualitative research. The research subjects were fifth grade students of SD Negeri Kp. Bulak III Pamulang Data collection techniques using instruments of observation, interviews, and documentation. The data analysis technique uses data reduction, data presentation, and conclusion drawing. From the results of the study it can be concluded that the Implementation of Character Education in Citizenship Education Subjects (PKn) begins with planning and implementation. The implementation of character education in the planning stage carries out the stages of deliberation to all parties, and its implementation has been running but there are still some things that must be improved in its implementation.